2003
DOI: 10.1109/tmtt.2003.814310
|View full text |Cite
|
Sign up to set email alerts
|

On a class of low-reflection transmission-line quasi-gaussian low-pass filters and their lumped-element approximations

Abstract: Gaussian-like filters are frequently used in digital signal transmission. Usually, these filters are made of lumped inductors and capacitors. In the stopband, these filters exhibit a high reflection, which can create unwanted signal interference. To prevent that, a new low-reflection ladder network is introduced that consist of resistors, inductors, and capacitors. The network models fictitious transmission lines with Gaussian-like amplitude characteristics. Starting from the analysis of this network, a proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…14, is suppressed by insertion of the memristor. LTspice model of the lossy quasi-Gaussian lowpass filter proposed by Djordjević et al [40] is shown in Fig. 19.…”
Section: Low-reflection Transmission-line Quasi-gaussian Lowpass Filtmentioning
confidence: 99%
“…14, is suppressed by insertion of the memristor. LTspice model of the lossy quasi-Gaussian lowpass filter proposed by Djordjević et al [40] is shown in Fig. 19.…”
Section: Low-reflection Transmission-line Quasi-gaussian Lowpass Filtmentioning
confidence: 99%
“…Low-Q lossy resonators are also used to achieve either one-port absorption [18]- [20] or symmetrical two-port absorption [21]- [25] for bandstop filters. Quasi-Gaussian lowpass filter prototypes are reported with both ports reflectionless because of the lossy components in the circuit [26], [27]. A 3.0-GHz distributed quasi-absorptive BPF is presented in [28] by using resistor-loaded lossy resonators as its first resonator to absorb reflection at only one side.…”
Section: Introductionmentioning
confidence: 99%
“…In practical circuit design, it is impossible to make RL/S 11 equals infinity, however, it is feasible to enhance the attenuation of S 11 for reducing the reflection to the source. The reflectionless filters [1][2][3][4][5][6][7][8] have been overlooked in the past time until recent years they obtain more and more attention.…”
Section: Introductionmentioning
confidence: 99%